Resilience under the chilling effect: how social support and digital media reshape online political participation among Chinese youth - Yang, Jiamei; Jiang, Hao; Dai, Mingjiang; Guo, Wodong (Frontiers in Psychology, 2025)
This study examines how digital media use and perceived social support influence political participation among Chinese youth. We administered a large survey (N = 6,855) and employed structural equation modeling (SEM) to test a theoretical path model. Key measures included self-reported intensity of digital media use, multidimensional perceived social support, and online political participation. The model hypothesized that social support directly predicts online political participation and also indirectly affects participation via digital media use, with perceived state presence moderating the model. Results indicate that higher perceived social support significantly predicts greater digital media use and higher levels of political participation. Digital media use partially mediates the positive effect of social support on participation. Moreover, stronger perceptions of state monitoring amplified the positive relationship between media use and engagement, consistent with expectations from a fragmented authoritarian context. These findings suggest that robust social support from local community and active online engagement jointly sustain youth civic involvement even under restrictive conditions. The study contributes empirical evidence on the dual role of online platforms and social support in Chinese political socialization, with implications for enhancing civic resilience in fragmented authoritarian settings.